Design, Service Quality, Facilities, Customer Satisfaction and Customer Preferences at Shopping Malls - Setiawan, Ricky; Sri Darma, Gede (School of Business, IPB University (SB-IPB), 2025)
Background: Indonesia’s economic growth has transformed consumer behavior, driving demand for malls that serve not only as retail centers but also as hubs for leisure, dining, and social interaction. In Bali, this trend is intensified by the mix of local residents and tourists with diverse expectations. The growing number of malls and rising competition highlight the need to identify key attributes that shape customer satisfaction and preferences, as misalignment may reduce competitiveness in the tourism-driven market.Purpose: This study aims to examine how design, service quality, and facilities influence customer satisfaction and preferences in modern shopping malls in Bali, and to assess the mediating role of customer satisfaction in these relationships.Design/methodology/approach: A quantitative research approach was adopted to test the conceptual framework. Data were obtained from 218 respondents who had visited three major shopping malls in Bali, selected through purposive sampling to ensure familiarity with multiple mall environments. A structured online questionnaire was using a Semantic Differential Scale captured perceptions of five latent variables: design, service quality, facilities, customer satisfaction, and customer preferences. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0, enabling the assessment of direct, indirect, and mediating effects in line with the Stimulus–Organism–Response (S-O-R) framework.Findings/Result: The results indicate that design and service quality significantly enhance customer satisfaction but do not directly influence customer preferences. Facilities emerge as the most influential factor, exerting a direct positive impact on preferences and an indirect effect through satisfaction. Customer satisfaction itself has a significant effect on preferences, underscoring its mediating role in linking mall attributes to behavioral intentions such as loyalty and revisit decisions.Conclusion: Customer satisfaction serves as a central bridge between mall attributes and customer preferences, underscoring the need for mall operators to invest in comprehensive facilities while maintaining high design standards and service quality to foster positive shopping experiences. In Bali’s tourism-driven retail sector, facilities that combine convenience, comfort, and leisure potential are pivotal to securing competitive advantage and encouraging repeat visits.Originality/value (State of the art): This research contributes to retail management literature by applying the Stimulus-Organism-Response (S-O-R) framework to integrate design, service quality, and facilities into a unified behavioral model explaining both satisfaction and preference formation. By focusing on a tourism-driven market, this study offers practical insights for mall operators, investors, and policymakers aiming to enhance customer experiences and strengthen brand loyalty. Keywords: design, service quality, facilities, customer satisfaction, customer preferences, shopping mall